Avaliação experimental da resistência de ligações em corte duplo em madeira com parafusos passantes - Silva Junior, Josué da (2017)
Wooden structures are an important alternative to growing demand for sustainability and reduced environmental impact from the construction industry. One of the limiting factors of carrying capacity of these structures are the strength of the connections between the elements that are composed, necessary to the deep study on the structural behavior of these connections. This paper presents to study different theoretical models of calculating connections strength through bolt with nut and washer in timber, quote, ABNT NBR 7190 (1997) and EUROCODE 5 (2008). Also it was conducted bond strength tests on standardized test specimens using two different species of wood, Garapeira (Apuleia leiocarpa) and Caixeta (Tabebuia cassinoides). The experimental results show that the model of the European Standard is more appropriate than the Brazilian Standard model for calculating the strength of bolted connections.